New Era Curriculum: Offline and Online Interactive Learning Has Been Effective ? - Ade Irma Suryani (LANGGAM: International Journal of Social Science Education, Art and Culture, 2023)
This look at objectives to determine: (1) differences in English studying effects among students who are taught the use of on line and offline getting to know media, (2) variations in mastering effects for college students who've open and closed interpersonal communication, (3) interactions between using learning media and interpersonal verbal exchange in influencing students' English gaining knowledge of outcomes. The quasi-experimental research method and through the necessities had been used, the research speculation has been tested the usage of 2-way ANOVA at a significance degree of α = 0.05 formerly executed the normality necessities test with Lilifors and the homogeneity of variance test with the Barlett take a look at and Fisher's check. The consequences of testing the hypothesis had been received: (1) the getting to know consequences of college students who are taught English the use of on-line studying media are better than offline learning media, that is indicated by means of Fcount = 6.596 Ftable = three.94, (2) the learning consequences of students who've open interpersonal communication has been better than closed interpersonal this is shown by Fcount = eleven.18 > Ftable = 3.94, and (three) there has been an interplay between the use of educational media and interpersonal conversation in influencing English studying outcomes, specifically Fcount = 68.38 Ftable = 3 ,94.